Marketing Technique in Healthcare Services: A Narrative Review - Monika Zade; Yugeshwari R Tiwade; Shivani Shahu; Gulshan Bandre; Sanket Surkar (Medsci Publications, 2024)
The marketing strategy used in tertiary care hospital medical services uses a variety of tactics to attract, keep, and engage patients. The primary objective is to provide patients with excellent medical care and positive practice. The methods are intended to increase the confidence and trustworthiness while giving them a unique and memorable experience. Digital marketing is one of the most critical marketing strategies for healthcare services. Social media, Search Engine Optimisation (SEO), and other powerful techniques are required to attract new patients and keep them interested in the hospital. Another strategy to encourage current patients to tell their friends about the hospital is to use patient referral programmes and word-of-mouth advertising. Implementing patient-centred services and individualized treatment is another tactical approach.